'Civility' and the Civilizing Project. (3rd May 2020) - Berenstain, Nora
Abstract: Calls for civility have been on the rise recently, as have presumptions that civility is both an academic virtue and a prerequisite for rational engagement and discussion among those who disagree. One imperative of epistemic decolonization is to unmask the ways that familiar conceptual resources are produced within and function to uphold a settler colonial epistemological framework. I argue that rhetorical deployments of 'civility' uphold settler colonialism by obscuring the systematic production of state violence against marginalized populations and Indigenous peoples, relying on the colonial conceptual framework of 'civilized' vs 'savage', and excusing death-promoting rhetoric under the guise of liberal disagreement.